1993
DOI: 10.1177/019459989310900309
|View full text |Cite
|
Sign up to set email alerts
|

Acute laryngeal trauma: A review of 77 patients

Abstract: Acute laryngeal trauma is a rare injury. In the past 18 years, 77 patients with acute laryngeal trauma have been evaluated at our institution. Each patient's care was overseen by the senior author (E.S.P.). The 61 patients who were seen within 48 hours of their accident are compared with those treated after 48 hours. All patients are classified by both injury (groups 1 through 5) and treatment (types I through III). Results are reported for voice, airway, and swallowing. Our methods of evaluation and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
1
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 21 publications
6
130
1
2
Order By: Relevance
“…Out of 19 cases, 16 cases (84%) were due to blunt trauma and 3 cases (16%) were due to penetrating trauma. These fi ndings are similar to those reported by Bent III et al [4] and Cohen and Larson et al [5].…”
Section: Discussionsupporting
confidence: 92%
“…Out of 19 cases, 16 cases (84%) were due to blunt trauma and 3 cases (16%) were due to penetrating trauma. These fi ndings are similar to those reported by Bent III et al [4] and Cohen and Larson et al [5].…”
Section: Discussionsupporting
confidence: 92%
“…As per the study prolonged intubation was found to be commonest cause of tracheal stenosis. This is in contrast to study of Bent III et al [1] and Cohen et al [2] where traumatic injury was the main cause of tracheal stenosis (Table 4).…”
Section: Resultscontrasting
confidence: 75%
“…According to Grillo, Mathesien, Wain study the two most common causes are post intubation and post tracheostomy [5]. Trauma was the most common cause of stenosis was proved in study reported by Bent III [6] and Cohen and Larsen [7].…”
Section: Etiopathogenesismentioning
confidence: 95%
“…Hence, barium esophagogram and/or esophagoscopy should be done to rule out esophageal disruption (3,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…These are make use of miniplates, wire or primary suturation for reconstruction of the laryngeal skeleton (14,16,17). We preferred to use primary suturation because there are some reports about fibrous healing especially with wire usage.…”
Section: Discussionmentioning
confidence: 99%